Development of a corporate university institution: strategic initiatives - Grigorievna, Bondarenko Tatiana; Alekseevna, Prodanova Natalia; Viktorovna, Sotnikova Lyudmila; Vladimirovna, Kosnikova Oksana (Linguistics and Culture Review, 2021)
This article is devoted to the study of the concept, methodological approach and problems of formation and development of the corporate university system. The article reveals the prerequisites for the creation of corporate universities, presents the Russian and international experience. The analysis of the current state of development of the corporate university system and existing strategic initiatives for the development of corporate universities is carried out. The authors of the article paid attention to the formation of a roadmap for the development of the institution of corporate universities, taking into account the impact of strategic initiatives using the advantages of the Learning management system.